Unraveling the Role of atsrt2 in Energy Metabolism, Stress Responses, and Gene Expression During Osmotic Stress in Arabidopsis Thaliana - Obrecht-Strnad, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Sirtuins participate in chromatin remodeling and gene expression regulation during stress responses. They are the only deacetylases that couple the cellular NAD+-dependent energy metabolism with transcriptional regulation. They catalyze the production of nicotinamide, inhibiting sirtuin 2 (SIR2) activity in vivo. The SIR2 homolog, AtSRT2, deacetylates non-histone proteins associated with mitochondrial energy metabolism. To date, AtSRT2 mechanisms during stress responses in Arabidopsis thaliana remain unclear. The transduction of mitochondrial metabolic signals links the energy status to transcriptional regulation, growth, and stress responses. These signals induce changes by regulating nuclear gene expression. The present study aimed to determine the role of SRT2 and its product nicotinamide in the development of A. thaliana and the expression of osmotic stress-response genes. Leaf development was greater in srt2+ plants than in the wild type, indicating that SET2 plays a role in energy metabolism. Treatment with polyethylene glycol activated and inhibited gene expression in srt2- and srt2+ lines, respectively. Therefore, we concluded that SRT2-stimulated plant growth and repressed signaling are associated with osmotic stress. © 2024 by the authors.